Rehabilitation after Distal Radius Fractures: Opportunities for Improvement - Meijer, Henriëtte A.W.; Obdeijn, Miryam C.; van Loon, Justin; van den Heuvel, Stein B.M.; van den Brink, Lianne C.; Schijven, Marlies P.; Goslings, J. Carel; Schepers, Tim (Journal of Wrist Surgery, 2023)
Background Exercises are frequently prescribed to regain function; yet there is no consensus on a standardized protocol, and adherence is low. Smart technology innovations, such as mobile applications, may be useful to provide home-based patient support in rehabilitation after distal radius fractures.Purposes Our purpose was to establish the potential of digital innovations for support and monitoring of patients and treatment adherence in rehabilitation programs, and additionally, to compare the current practice among physiotherapists to the various wrist exercise regimens and their effectiveness as described in the literature.Methods Standard practice, including the use of support tools for treatment adherence, was evaluated using a nationwide survey. Then, scientific databases were searched using “distal radius fracture” and “physiotherapy” or “exercise therapy,” and related search terms, up until 23 March 2023. Results of the survey and literature review were compared.Results The survey was completed by 92 therapists. Nonstandardized support tools were used by 81.6% of respondents; 53.2% used some form of technology, including taking photos on the patients' smartphone for home reference. In the literature review, 23 studies were included, of which five described an exercise protocol. Treatment adherence was not reported in any of the included studies. Two studies described the use of smart technology or support tools.Conclusions There is no consensus on a standardized exercise protocol for rehabilitation after distal radius fractures, neither from a systematic literature search nor from a nationwide survey. Smart technology may facilitate monitoring of patients and exercise adherence, hereby supporting self-efficacy and improving adherence and outcomes.
Keywords: wrist fractures; exercise therapy; treatment adherence; gamification; self-efficacy